Modelling the Implications of Delayed Payments on Contractors’ Cashflows on Infrastructure Projects - Aaron Chadee; Hanna Ali; Sihara Gallage; Upaka Rathnayake (Salehan Institute of Higher Education, 2023)
The consideration of payments to contractors is not only a legal obligation but a necessity for assuring the continuity and completion of a construction project. However, consistent payments to facilitate project cash flows are uncommon in the construction industry. Within the context of a small island developing state, this paper aims to uncover leading risks factors the contributing to implications of delayed payments, on contractors’ cash flows and uncover any causalities and effects on relationships among these factors. A two-tiered quantitative approach was adopted. Firstly, a compiled list of delay factors was collated from the literature review. Semi-structured interviews were conducted with experienced construction professionals to determine the factors’ relevance and applicability in Trinidad and Tobago. A closed-ended survey questionnaire was subsequently developed and administered to primary construction stakeholders. Secondly, the responses obtained were collated, validated, and ranked using the relative importance index. A confirmatory factor analysis (CFA) was carried out using SPSS, and thereafter, SPSS Amos was used to determine the best-fit Structural Equation Model (SEM). The results strongly indicate that the issue of delayed payments is very prevalent within public sector projects. Unstable political climates and the delay in employers’ issuance of variation orders were found to be the main causes of delayed payments within the industry. Delays in sub-contractor and supplier payments as well as an increase in the contractor’s debt are the leading effects of delayed payments on the contractor’s cash flows. Based on these findings, a risk response framework was outlined to assist small to medium-contracting enterprises cope with payment delays, both locally and internationally. This research contributes to the advancement of construction management knowledge by informing construction professionals and policy makers of the implications of delaying approved payments, the consequential causes and effects, and a risk response technique to mitigate the negative effects on contractors’ cash flows. Doi: 10.28991/CEJ-2023-09-01-05 Full Text: PDF